Exploring the longitudinal relationships between non-suicidal self-injury and depressive symptoms in adolescents: a cross-lagged panel network analysis - Qiannan Jia; Zhongying Wu; Bin Liu; Yuting Feng; Wei Liang; Danxia Liu; Lei Song; Caina Li; Qun Yang (BMC Psychiatry)
Abstract Background Non-suicidal self-injury (NSSI) and depressive symptoms are two major public health issues among adolescents. Moreover, they can often co-occur, which can lead to additional negative outcomes, such as suicidal behaviors. Therefore, this study aimed to explore the comorbidity patterns of NSSI and depressive symptoms and provide valuable insights for future interventions. Methods This study examined the relationship between NSSI and depressive symptoms via a cross-lagged panel network (CLPN). A total of 866 Chinese junior high school students (39.80% girls, M age = 12.73 years, SD = 0.43) completed measurements during three time points. Results Comorbidity rates of NSSI and depressive symptoms ranged from 10.51 to 15.13% among the adolescents. Moreover, results of the CLPN indicated that somatic and retarded activity, depressive affect, and lack of positive affect were strongly and positively associated with multiple NSSI behaviors. Conversely, burning from the NSSI cluster could negatively predict somatic and retarded activity and depressive affect. In addition, somatic and retarded activity and depressed affect were bridge symptoms that linked the comorbidity between NSSI and depressive symptoms. Conclusion These results demonstrate a negative reinforcement feedback pathway between NSSI and depressive symptoms, which provides evidence for intrapersonal negative reinforcement of NSSI. Furthermore, these findings identify the core and bridge symptoms between NSSI and depressive symptoms, which can provide new ideas for subsequent intervention treatments.